Pengaruh Komunikasi Pemasaran Terhadap Citra Perusahaan Jasa Penyewaan Alat Berat Pada PT. Buana Oto Mandiri - Anna N. Madengke; Harry J. Sumampouw; Aneke Y. Punuindoong (Universitas Sam Ratulangi, 2017)
This research is motivated by the problems found in PT. Buana Oto Mandiri company, which there is a lack of public communication or communication to the public in the company's introduction and understanding of corporate image. The purpose of this study is to know the marketing communication whether there is influence on the image of heavy equipment rental companies at PT. Buana Oto Mandiri. Lack of public communication will have an effect and create a lack of trust from consumers in using the services of the company as a result will impact on the image of the company will decline. Therefore, it is necessary to have good communication to the community. Attractive and efficient communication will create trust by the public public to the company. And in the end there will be an increasing demand of heavy equipment rental services offered by the company. In this research, the method used is descriptive quantitative research method by spreading questionnaire 75 respondents who become sample in this research. The data were collected by questionnaires that have been tested for their validity and reliability. And writerâ€™s data analysis is descriptive and inferential statistic, consisting of simple correlation coefficient and regression done by using program SPSS for windows version 23.0. The results showed that there is a significant influence between marketing communications on corporate image at PT. Buana Oto Mandiri and this means the work hypothesis or alternative hypothesis accepted. This means there is a positive influence between marketing communications to corporate image with a level of influence of 30.3%. For suggestions, companies are expected to maintain marketing communications because of the company's influential image in order to improve leasing.Â Keywords: Marketing comunication, corporate image.